Influence of motivation towards sports in alcohol, tobacco and cannabis consumption in adolescent students - Usán, Pablo (2017)
One of the most serious problems faced by our society is the use of drugs by young people. Sports practice can act as a preventive factor being one of the most representative habits of a healthy lifestyle. Therefore, the objective of the study is to analyze the relationship and influence of motivation towards sports practice in the consumption of alcohol, tobacco and cannabis of school sports adolescents. The results reveal significant influences of intrinsic, extrinsic motivations and lack of motivation in the different prevalence of consumption in more or less self-determined and adaptive behavior patterns.